Analysing the effects of sliding, adhesive contact on the deformation and stresses induced within a multi-layered elastic solid. (October 2016) - Chong, W.W.F.; Chidlow, S.J.
Highlights: A mathematical model is presented for a sliding, adhering contact between a rigid parabolic indenter and a multi-layered elastic solid. The adhesive forces are modelled using Lennard-Jones potential and an iterative algorithm is proposed, solving for the contact pressure, surface displacement and subsurface stresses resultant within the layered solid. This paper demonstrates the significance of having a suitable mathematical representation for the traction distribution along the sliding, adhering contact. Graphical abstract: Abstract: This paper presents a mathematical model of sliding, adhering contact between a rigid parabolic indenter and a multi-layered elastic solid, which is assumed to comprise of a homogeneous coating bonded through a functionally-graded transitional layer to a homogeneous substrate. The adhesive forces in this investigation are modelled using Lennard-Jones potential and an iterative algorithm is proposed that solves for the contact pressure, surface displacement and sub-surface stresses resultant within the layered solid. The effects of surface adhesion and different material properties such as varying coating/transition layer thickness and coating hardness on the solution of the contact problem are subsequently investigated in detail. The numerical approach presented in this paper demonstrates the significance of having a suitable mathematical representation for the traction distribution along the sliding, adhering contact. It is found that under weakly adhering conditions, the assumption of only Coulombic traction suffices to determine the displacements and subsurface stresses within the multi-layered solid. However, it is noted that stress concentrations within the material begin to propagate through all three layers of the elastic solid with increased surface adhesion, which could potentially induce plasticity and lead to material ploughing under sliding. The proposed model allows us to further investigate and improve our understanding of the combined effects of traction and boundary adhesion in sliding contacts, which can be used to inform the design of materials needed in such conditions.